The Effectiveness of Reducing COD, TSS, and Detergent using Banana Stem Filter Media in the Wastewater Treatment of Motor Vehicles Waste Treatment - Yustika Kusumawardani; Soehartono Soehartono; Sri Subekti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The development of the area around the river continues to increase in line with the pace of development to improve community welfare. Likewise, with small-scale motorized vehicle washing businesses that are widely located on the riverbank, if there is no processing, there is a concern that it will also pollute the river. One of the requirements for an effective wastewater treatment plant is minimal maintenance and costs and safe and easy operation. The cellulose content and hygroscopic ability of banana stems make banana stems usable as a porous medium. Based on previous research, banana stem filter media can reduce TSS concentration and detergent for motorized vehicle washing wastewater. This research uses descriptive quantitative research methods. The test variables were the concentrations of COD, TSS, and detergent. This study aims to design WWTP using banana stem filters and to determine the effectiveness of WWTP in reducing the test parameters. The analysis results show that the WWTP of banana stem filter media can be used to treat motorized vehicle washing wastewater with an average value of the effectiveness of reducing the overall test parameters by 51%. The percentage of the best reduction effectiveness was 77% in the TSS parameter on day 4. The average reduction effectiveness of each COD parameter was 48%, TSS 55%, and detergent was 51%.